Green discolouration of urine following propofol infusion in a dog. (25th May 2017) - Flaherty, D.; Auckburally, A.
Abstract : A three‐year‐old, female neutered Weimaraner was presented with a history of neck pain and tetraparesis. MRI revealed an extradural mass at the level of C3 vertebra, which was thought to be a spinal abscess, and the dog was scheduled for surgical exploration the following morning. Overnight the dog developed an exaggerated ventilatory pattern, with paradoxical inward movement of the thorax on inspiration. Arterial blood gas analysis revealed respiratory acidosis and ventilator support was initiated to prevent excessive respiratory fatigue. During mechanical ventilation, anaesthesia was maintained using a propofol target‐controlled infusion system and, subsequently, the dog produced bright green urine in the urine collection system. Although previously documented in humans, this appears to be the first report of green urine in a dog following propofol use.